Association of candidate gene polymorphisms with clinical subtypes of preterm birth in a Latin American population - Gimenez, Lucas G. (2016)
Background. Preterm birth (PTB) is the leading cause of neonatal mortality and morbidity. PTB is often classified according to clinical presentation: Idiopathic (PTB-I), preterm premature rupture of membranes (PTB-PPROM), and medically induced (PTBM). The aim of this study was to evaluate the associations between specific candidate genes and clinical subtypes of PTB. Methods. 24 SNPs were genotyped in 18 candidate genes in 709 infant triads. Of them, 243 were PTB-I, 256 PTB-PPROM, and 210 PTB-M. These data were analyzed with a Family-Based Association. Results. PTB was nominally associated with rs2272365 in PON1, rs883319 in KCNN3, rs4458044 in CRHR1, and rs610277 in F3. Regarding clinical subtypes analysis, 3 SNPs were associated with PTB-I (rs2272365 in PON1, rs10178458 in COL4A3, and rs4458044 in CRHR1), rs610277 in F3 was associated with PTBPPROM, and rs883319 in KCNN3 and rs610277 in F3 were associated with PTB-M. Conclusions. Our study identified polymorphisms potentially associated with specific clinical subtypes of PTB in this Latin American population. These results could suggest a specific role of such genes in the mechanisms involved in each clinical subtype. Further studies are required to confirm our results and to determine the role of these genes in the pathophysiology of clinical subtypes.